1985
DOI: 10.1507/endocrj1954.32.337
|View full text |Cite
|
Sign up to set email alerts
|

A malignant pheochromocytoma with ileus, polyuria and hypercalcemia: A case of recurrence 17 years after the initial operation.

Abstract: A case of malignant pheochromocytoma, with a recurrence 17 years after the initial diagnosis of benign pheochromocytoma, was presented. The autopsy revealed multiple metastases of pheochromocytoma to the bone marrow of the thoracic and lumbar vertebrae. Of particular note is the fact that the patient was associated with paralytic ileus, polyuria and hypercalcemia and that he died of hypercalcemia crisis. Cases like this appear to be very rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The paucity of cohort studies with a long-term follow-up is probably due to the fact that SDH gene mutations have only been described quite recently. However, it is reported that metastatic disease can occur up to 20 years after initial diagnosis of PGL 53 54. The lack of long-term follow-up in the two included cohort studies may have resulted in an underestimation of the incidence of malignant PGL.…”
Section: Discussionmentioning
confidence: 96%
“…The paucity of cohort studies with a long-term follow-up is probably due to the fact that SDH gene mutations have only been described quite recently. However, it is reported that metastatic disease can occur up to 20 years after initial diagnosis of PGL 53 54. The lack of long-term follow-up in the two included cohort studies may have resulted in an underestimation of the incidence of malignant PGL.…”
Section: Discussionmentioning
confidence: 96%
“…Since malignant disease can occur 17 or more years after diagnosis of the initial tumor, with patients asymptomatic during this interval, 11,12 it is realistic to assume that some tumors classified as benign in this study may later turn out to metastasize. Such misclassification may lead to a diminished yield of differentially expressed genes, but would not be expected to result in any increase in falsepositive rates of gene detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of acute abdominal emergencies such as paralytic ileus [7, 8, 9, 10, 11, 12], pseudo-obstruction [6, 13, 14], intestinal ischemia and necrosis [15, 16, 17, 18, 19], gastrointestinal bleeding [20], and perforation of the colon [13, 14]appears to be very rare. The prognosis of patients with these gastrointestinal manifestations is poor because of the increased risk from failing to establish the correct diagnosis or from proceeding with surgical exploration, while unaware of the presence of a pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…As to the preoperative preparation, phentolamine among various alpha- or beta-adrenergic receptor blocking agents may be recommended. Of the 12 cases of pheochromocytoma associated with ileus treated with alpha- or beta-adrenergic receptor blocking agents for improving blood pressure and ileus [6, 7, 8, 9, 10, 11, 12, 13, 14, 17], 7 cases showed improvement in ileus. Especially, the use of phentolamine alone or in combination with other adrenergic receptor blocking agents appears to be effective [6, 7, 8, 10, 13].…”
Section: Discussionmentioning
confidence: 99%